The Impact of Buy Now Pay Later on Consumer Behavior: A Systematic Literature Review and Bibliometric Analysis - Munoz Valenciano, Oscar; Mora Cruz, Alexandra; Sanchez Pereira, Melany; Montero Ulloa, Diana (LACCEI, 2025)
ABSTRACT- This study explores the academic landscape of Buy Now Pay Later services via a systematic literature review and bibliometric analysis. Fifty peer-reviewed articles from Scopus and Web of Science were analyzed to identify key contributors, conceptual trends, and research gaps. The results reveal a growing interest in BNPL, particularly in fintech-driven economies, following the onset of the pandemic. Topic modeling with Latent Dirichlet Allocation (LDA) revealed two main themes: (1) the integration of BNPL into the financial ecosystem and (2) the behavioral factors that influence adoption. The findings suggest that Buy Now Pay Later reshapes consumption habits by decoupling purchases from payments, thereby increasing impulsivity and financial vulnerability. This study contributes to financial behavior theory by integrating technological, psychological, and sociodemographic factors. From a practical perspective, the study highlights the need for regulation, ethical digital marketing, and financial education to mitigate associated risks. The methodology provides a replicable framework for analyzing emerging fintech innovations and their societal implications.